1993
DOI: 10.1111/j.1751-1097.1993.tb02294.x
|View full text |Cite
|
Sign up to set email alerts
|

REGULATION OF UV‐PROTECTIVE PIGMENT SYNTHESIS IN THE EIPERMAL LAYER OF RYE SEEDLINGS (Secale cereale L. cv. KUSTRO)

Abstract: Trans‐cinnamic acid is the product of the L‐phenylalanine ammonia lyase (PAL, EC 4.3.1.5) enzyme reaction and might regulate the subsequent phenylpropanoid synthesis by feedback inhibition of PAL activity. The partial conversion of trans‐cinnamic acids (e.g. trans‐p‐coumaric acid) and of trans‐p‐coumaryl‐glucoside (chemically synthesized model substance for cinnamic acid derivatives) to the cis isomers upon UV irradiation leads to reduced inhibition of PAL activity within minutes. In rye leaves this rapid enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 36 publications
2
24
0
1
Order By: Relevance
“…Increased accumulation of phenolic compounds is one of the best characterized responses to UV-B radiation; these compounds contribute to filter out UV-B photons before they reach sensitive molecules in the mesophyll (Braun and Tevini, 1993;Landry et al, 1995;Reuber et al, 1996;Bilger et al, 1997;Barnes et al, 2000;Mazza et al, 2000). Soluble phenolic compounds are often also induced in response to insect herbivory, and they are thought to play a role as direct antiherbivore defenses (Elliger et al, 1981;Stamp and Osier, 1998;Hoffland et al, 2000;Leitner et al, 2005;Izaguirre et al, 2006).…”
mentioning
confidence: 99%
“…Increased accumulation of phenolic compounds is one of the best characterized responses to UV-B radiation; these compounds contribute to filter out UV-B photons before they reach sensitive molecules in the mesophyll (Braun and Tevini, 1993;Landry et al, 1995;Reuber et al, 1996;Bilger et al, 1997;Barnes et al, 2000;Mazza et al, 2000). Soluble phenolic compounds are often also induced in response to insect herbivory, and they are thought to play a role as direct antiherbivore defenses (Elliger et al, 1981;Stamp and Osier, 1998;Hoffland et al, 2000;Leitner et al, 2005;Izaguirre et al, 2006).…”
mentioning
confidence: 99%
“…Optimally, a leaf's structure would allow the penetration of photosynthetically active light to the interior while limiting the penetration of harmful UV rays. In fact, considerable evidence exists that penetration of UV-B radiation is strongly reduced by UV-absorbing compounds, chiefly flavonoids, in epidermal tissues (Robberecht andCaldwell, 1978, 1983;Tevini et al, 1991;Braun and Tevini, 1993;Day et al, 1993;Stapleton and Walbot, 1994). However, in herbaceous annuals UV-screening pigments are restricted mainly to the vacuoles of the epidermal cells, and UV-B can leak into the interior of the leaf along the anticlinal walls (Day et al, 1993).…”
mentioning
confidence: 99%
“…The UV-B light-absorbing flavonoids are implicated as protective pigments in shoots and leaves exposed to UV-B light, and their specific location in the epidermal layer protects intemal cell layers by attenuating the impinging UV-B radiation at the epidermis (Tevini et al, 1991;Braun and Tevini, 1993). It has been shown that the photoinduced accumulation of these flavonoids is preceded by an indixtion of severa1 enzymes of phenylpropanoid biosynthetic pathway such as PAL and chalcone synthase of the flavonoid biosynthetic pathway (Hahlbrock and Scheel, 1989;Schmelzer et al, 1989).…”
mentioning
confidence: 99%